BLOOD STOP DRUGS IN EMERGENCY MEDICAL CARE - Egamberdiyev Jasurbek Jumanazar ogli; Usmonov Dilshodbek Abdumalikovich; Nurmatov Nurmuxammad Jaloldin ogli; Usmonov Odil Sidiqovich; Abdugofurov Ilhomidin Abduna'im ogli (Scholar Express Journals, 2022)
Dear reader, in this article you can get information about what drugs we can help faster if we use to provide first aid at the time of bleeding, one of the most frequent cases of the moment
Keywords: Blood , Drug , Gastrointestinal , Thrombin